Evaluation of CERES and CloudSat Surface Radiative Fluxes Over Macquarie Island, the Southern Ocean. Issue 9 (16th September 2020) - Hinkelman, Laura M.; Marchand, Roger
Abstract: Many studies involving surface radiative fluxes rely on surface fluxes retrieved by the Clouds and the Earth's Radiant Energy System (CERES) project or derived from spaceborne cloud radar and lidar observations (CloudSat‐CALIPSO). In particular, most climate models that participated in the Coupled Model Intercomparison Project Phase 5 (CMIP5) were found to have too little shortwave (SW) radiation being reflected back to space and excessive SW radiation reaching the surface over the Southern Ocean—an error with significant consequences for predicting both regional and global climate. There have been few evaluations of CERES or CloudSat retrievals over the Southern Ocean. In this article, CERES and CloudSat retrieved surface SW and longwave (LW) downwelling fluxes are evaluated using surface observations collected over the Southern Ocean during the Macquarie Island Cloud and Radiation Experiment (MICRE). Overall, biases (CERES—surface observations) in the CERES‐surface fluxes are found to be slightly larger over Macquarie Island than most other regions, approximately +10 W m −2 for the SW and −10 W m −2 for the LW in the annual mean, but with significant seasonal and diurnal variations. If the Macquarie observations are representative of the larger SO, these results imply that CMIP5 model errors in SW surface fluxes are (if anything) somewhat larger than previous evaluation studies suggest. The bias in LW surface flux shows a marked increase at night, which explains most of the total LW bias. The nighttime bias is due to poor representation of cloud base associated with low clouds. Plain Language Summary: We compare satellite estimates for the amount of sunlight (solar) and thermal (infrared) energy reaching the surface, with surface observations collected at Macquarie Island. Macquarie Island is located in the Southern Ocean (SO) about halfway between New Zealand and Antarctica. The satellite‐based estimates have seen little evaluation over the SO. This is a concern because climate models, when compared with the satellite estimates, have too much sunlight reaching the surface, which has important implications for simulating the current climate and climate changes. The comparison shows that the satellite estimates are reasonably good, but the differences between the satellite estimates and the surface measurements are somewhat larger at Macquarie than at most other locations. The data suggest that (if anything) the model errors with respect to having too much sunlight reaching the surface are slightly larger than current studies suggest. The amount of infrared energy coming from the atmosphere is also critical to the surface temperature (surface energy balance). In the infrared, the satellite errors are of similar magnitude and are due to a systematic overestimation of the altitude of cloud base at night. In general, the satellite errors in both the solar and infrared flux estimates have strong seasonal and diurnal variations that need to be addressed. Key Points: CERES and CloudSat‐CALIPSO surface shortwave (SW) and longwave (LW) fluxes are compared with observations from Macquarie (Southern Ocean) Mean CERES srf fluxes are larger in SW (+10 W m −2 ) and smaller in LW (−10 W m −2 ) than observed with significant seasonal and diurnal variations LW surface fluxes are smaller at night (−16 W m −2 ), which explains most of the total bias and is due to incorrect cloud base for low clouds